ROLE OF RUBBER BAND LIGATION AS A NON-INVASIVE TREATMENT IN HAEMORRHOID W.S.R. TO INTERNAL HAEMORRHOIDS (International Journal of Ayurveda and Pharma Research, 2020)
In the present modern age,the majority of people are suffering from haemorrhoids. Mithyaahara- Vihara (faulty food habits and improper sedentary lifestyle) has increased its incidence. Internal haemorrhoid is situated internal to anal orifice, starts at anorectal ring and ends at the dentate line. Haemorrhoidectomy either open or closed is an invasive procedure for the treatment of hemorrhoids. A non-invasive measure for the treatment of haemorrhoids is Rubber Band Ligation. In this method, internal haemorrhoids are tied off at its base with rubber bands to cutting off blood flow resulting in necrosis of the haemorrhoidal stump. It relies on the principle of mucosal fixation. In the present clinical study Rubber Band, Ligation was done in randomly selected 15 patients of either sex with internal haemorrhoids. The duration of the trial was of 15 days, with a follow-up of 4 weeks. The total effect of therapy was assessed based on Clinical &Postoperative criteria. Statistical analysis has determined significance of the treatment. For all values significance level was p